Analysis of Factors That Influence the Use of Social Media Analytic Debi Using UTAUT Model - Muhammad Hadi Edrus Alaydrus; Togar Alam Napitupulu (Universitas Bina Darma, 2022)
Social media has provided consumers with new opportunities to engage in social interactions on the internet. The very high increase in the number of social media users has provided a new market for companies that can be seen as new business opportunities. Digital Brand Index or also called DEBI is a social media Analytic developed by limadigit agency in 2014 which aims to be a unique selling point for the agency. This study aims to determine what factors influence the behavior of using social media Analytic DEBI using the Unified Theory of Acceptance and Use of Technology method (UTAUT). The Conclusion of this study is behavioral intention has a significant effect on use behavior, performance expectancy doesn’t has a significant effect on behavioral intention, effort expectancy doesn’t has a significant effect on behavioral intention, facilitating condition has a significant effect on behavioral intention, information quality doesn’t has a significant effect on behavioral intention, existing features has a significant effect on behavioral intention, based on the conclusion, the factors that influence the use behavior of DEBI are behavioral intention, facilitating condition and existing features.